Effectivity Test of Tobacco Leaf (nicotiana tabacum l.) 96% Ethanol Extract on Culex Quinquefasciatus Larvae Mortality - Ahmad Rosid Nasrulloh Arifqi; Devi Usdiana Rosyidah; Listyana Masyita Dewi; E. M. Sutrisna (Universitas Muhammadiyah Malang, 2020)
Culex quinquefasciatus acts as a vector for Filariasis disease. The transmission of this disease can be prevented by cutting the life cycle of these mosquitoes at the larvae phase. Tobacco leaf contains an alkaloid, flavonoid, essential oil, saponin, and tannin which can kill Culex quinquefasciatus larvae. This study is a laboratory experiment with a post-test only controlled group design. This study used the larvae of Culex quinquefasciatus third-instar larvae. Six hundreds larvae were divided into 6 groups and 4 repetitions (each consisted of 25 larvae), i.e. negative control (distilled water + CMC), tobacco leaf ethanol extract (EEDT) with 0.025%; 0.05%; 0.075% and 0.1% doses and positive control (temephos). The number of dead larvae was counted at 6, 12, 18, and 24 hours after treatment. The results of the Kruskal-Wallis test showed p-value = 0.000, followed by the Mann-Whitney Post-hoc test, which resulted in all four doses of EEDT significantly differed compared to the negative control. However, 0.1% concentration was insignificantly different than the positive control. This showed that the ethanol extract of Nicotiana tabacum L. was effective in killing Culex quinquefasciatus larvae and EEDT with 0.1% concentration had the same potential as temephos as a larvicide.